TENTANG KONSEP KEBUDAYAAN - Kistanto, Nurdien Harry (Fakultas Ilmu Budaya Universitas Diponegoro, 2015)
Human consciousness towards the experience encouraged him composing formulation, definitions, and theories about the ways of his life, into the conception about culture. Consciousness thus commenced from the gift of reason, his human instincts and feelings, which are not owned by other beings, such as animals. Leslie White (1973), defined the conception of culture that includes